Crack growth at fastener holes containing intergranular cracking. Issue 10 (27th February 2017) - Lo, M.; Jones, R.; Bowler, A.; Dorman, M.; Edwards, D.
Abstract: This paper examines the growth of cracks at a fastener hole containing intergranular cracking with a focus on 'dome nut hole' coupons that are representative of a critical location in the Royal Australian Air Force AP‐3C Orion wing. It is shown that crack growth under operational flight loads can be captured using the NASGRO formulation and that the scatter in these various tests can also be captured by allowing for small variations in the value of the cyclic stress intensity fatigue threshold. In this context, it is shown that crack growth can be captured using both a cycle‐by‐cycle analysis and also a United States Air Force 'characteristic K' approach. We also see that, for the operational load spectra considered, the crack growth history is approximately exponential so that the United States Air Force risk assessment computer program (PRobability Of Fracture) can be used to assess the risk of failure by fracture. The results of this study also suggest that, provided that intergranular cracking does not turn and break through to a free surface, it should have little effect on crack growth at a fastener hole.